2017
DOI: 10.1080/2000656x.2016.1254642
|View full text |Cite
|
Sign up to set email alerts
|

Scandcleft randomised trials of primary surgery for unilateral cleft lip and palate: 10. Parental perceptions of appearance and treatment outcomes in their 5-year-old child

Abstract: Results:The results indicated that the majority of parents were satisfied with cleft-related features of their child's appearance. Further, most children coped well with treatment according to their parents. Nevertheless, 17.5% of the children showed minor or short-term reactions after treatment experiences, and 2% had major or lasting difficulties. There were no significant relationships between parent perceptions of treatment-related problems and the occurrence of post-surgical medical complications. Conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…On the whole, participants in the current study reported a high level of satisfaction with the health-care that they and their child had received following a diagnosis of CL/P. This finding is in line with previous CL/P research (Damiano et al, 2006; Nelson & Kirk, 2013; Feragen et al, 2017) and the wider pediatric literature (Cousino & Hazen, 2013), and provides a positive overall view of the health services relevant to CL/P. Health-care satisfaction is a key predictor of overall familial well-being (Stock et al, 2019a), and as such should be systematically monitored and maintained.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the whole, participants in the current study reported a high level of satisfaction with the health-care that they and their child had received following a diagnosis of CL/P. This finding is in line with previous CL/P research (Damiano et al, 2006; Nelson & Kirk, 2013; Feragen et al, 2017) and the wider pediatric literature (Cousino & Hazen, 2013), and provides a positive overall view of the health services relevant to CL/P. Health-care satisfaction is a key predictor of overall familial well-being (Stock et al, 2019a), and as such should be systematically monitored and maintained.…”
Section: Discussionsupporting
confidence: 91%
“…This may reflect the understanding that health-care satisfaction can be a challenging construct to measure, and that the collation of “total scores” often results in a “ceiling effect” (Moret et al, 2007). Although previous findings suggest that parents rate CL/P health-care positively on the whole (Damiano et al, 2006; Nelson & Kirk, 2013; Feragen et al, 2017), the views of parents who are less satisfied remain unheard, and knowledge of which particular aspects of care parents are satisfied and dissatisfied with is scarce.…”
Section: Introductionmentioning
confidence: 96%
“…Several studies have investigated the social and emotional difficulties among parents caring for children with clefts, such as anxiety, depression and poor psychological 'adjustment' [4,[9][10][11]. However, there is still a lack of studies investigating these experiences faced by parents and/or caregivers of children with CL/P in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has indicated that families value health professionals’ expertise and interpersonal skills, as well as the continuity and coordination of care (Knapke et al, 2010; Nelson and Kirk, 2013). Although the service provided by the specialist craniofacial teams is consistently highly rated (Nelson and Kirk, 2013; Feragen et al, 2017), previous research has demonstrated parental dissatisfaction with the care delivered by nonspecialist health professionals. During the diagnostic experience, parents have reported a lack of knowledge among nonspecialists about these conditions and their long-term implications, and/or the delivery of inaccurate, inconsistent, or overwhelming information (Stock and Rumsey, 2015; Searle et al, 2016; Searle et al, 2018; Costa et al, 2019; Stock et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%